Exploring consumer preferences on blended donkey milk yogurt in Zimbabwe - Mutizhe, Erick (BUSE, 2024)
This study sought to explore the consumer preferences towards the novel blended donkey milk yoghurt in Zimbabwe. Convenience sampling (Snowball) was done to identify participants from 110 donkey owning households in 3 wards in Beitbridge District of Zimbabwe. The participants responded to a pre-tested researcher administered questionnaire. Knowledge, attitude and practices were evaluated employing the KAP framework. Furthermore, Spearman rank correlation was used to evaluate associations between knowledge-attitudes (K-A), knowledge-practices (K-P) and attitudes-practices (A-P) of consumers on donkey milk products. Blended donkey milk yoghurts were made using documented standard protocols and 54 consenting volunteers were purposively selected to participate in sensory evaluation of ginger, honey and baobab donkey milk yoghurt blends. Chi-square tests were done to determine the associations between the consumer characteristics and the consumer donkey milk blend preferences. Strong positive correlations between K-A, KP and A-P with correlation coefficients 0.793, 0.715 and 0.884 respectively with p<0.01 were observed. The findings indicate that a greater knowledge of donkey milk products contribute to positive attitudes towards consumption. Factors that affected consumer preferences for the blended donkey milk yoghurt were analysed using multilinear logistic regression. Education, age, price, health consciousness, male gender and product availability were important predictors for choosing ginger. Taste was an important predictor for baobab yoghurt blend preference whereas income levels affected choice of honey blend. Sensory evaluation revealed that the most preferred yoghurt was the ginger blend. Gender had statistically significant association with liking of ginger (χ2 = 8.276; ρ<0.05); baobab (χ2 = 7.721; ρ<0.05) and honey (χ2 = 9.382; ρ<0.05) blended donkey milk yoghurts. Age had a statistically significant association with consumer preferring the ginger (χ2 = 8.276; ρ<0.05); baobab (χ2 = 7.721; ρ<0.05) and honey (χ2 = 9.382; ρ<0.05) blended donkey. There was however no statistically significant association between income, family size and yoghurt eating frequencies. There is need to consider taste preferences, age and gender dynamics in marketing yoghurt blends. It is recommended that market segmentation, price sensitivity, awareness raising and ensuring constant availability of donkey milk products on the market be prioritized to counter some forces against the successful introduction and growth of blended donkey milk yoghurt in the marketspace. Keywords: Donkey; Yoghurt blend; Preference; Multinominal, Chi-Square
Keywords: Donkey milk yoghurt; Blended yoghurt